WORK-LIFE BALANCE AND JOB SATISFACTION: EVIDENCE FROM THE INDONESIAN BANKING SECTOR - Siti Sahara (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2025)
This study investigates the relationship between work-life balance (WLB) and job satisfaction (JS) within the Indonesian banking sector, an industry characterized by high performance demands and rapid digital transformation. Using a quantitative design, data were collected from 400 employees across state-owned and private banks through validated instruments measuring WLB and JS. Descriptive statistics, Pearson correlation, and regression analysis were employed, complemented by thematic analysis of qualitative responses. The findings reveal a strong positive correlation between WLB and JS (r = 0.65, p < 0.05). Employees with access to flexible work arrangements and supportive organizational cultures reported significantly higher levels of satisfaction compared to those under rigid structures. However, the results also highlight demographic variations: younger employees valued career advancement and compensation as strongly as WLB, suggesting that balance alone does not guarantee satisfaction. Qualitative evidence further indicates that managerial support and cultural norms—particularly those emphasizing long working hours—remain critical determinants of employee well-being. This study contributes to the literature by extending empirical evidence of the WLB–JS nexus to the Indonesian banking context, which has been underrepresented compared to Western economies. Practically, the findings underscore the need for banks to adopt holistic human resource strategies, integrating flexible policies, wellness programs, and career development pathways. For policymakers, the results highlight the importance of regulatory frameworks that foster sustainable work environments. By aligning employee well-being with organizational resilience, WLB emerges as both a driver of job satisfaction and a source of competitive advantage in the financial sector.